2022
DOI: 10.20944/preprints202206.0127.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Digital Transition in Rural Emergency Medicine: Impact of Job Satisfaction and Workload on Communication and Technology Acceptance

Abstract: Background: Tele-emergency physicians (TEPs) take an increasingly important role in the need-oriented provision of emergency patient care. To improve emergency medicine in rural areas, we set up the project Land|Rettung (English: Rural|Rescue), which uses TEPs to restructure professional rescue services using information and communication technologies (ICTs) in order to reduce the therapy-free interval. Successful implementation of ICTs relies on user acceptance and knowledge sharing behavior. Methods and find… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In other preliminary studies the PhysicianPlus scale which is based on the well-known employees promotor scale was already used in the same setting (Hasebrook et al, 2016b;Hinkelmann et al, 2017;Hahnenkamp et al, 2018) but also in different settings such as the project "rural/rescue". (Hasebrook et al, 2022) Here, the scale was found to be highly reliable with an Cronbach's Alpha of 0.91 while in prior studies in the same present setting, the reliability was examined to lay at 0.78. (Hahnenkamp et al, 2018) In this study, mean ratings show a positive attitude and vary between 1.5 and 3.4 (with 1 o 5 indicating a more positive and 6 to 10 a more negative evaluation) with "purposeful work" being the best and "demanding working hours" the worst evaluation (see table 9).…”
Section: Physicianplus Satisfaction Scalementioning
confidence: 66%
“…In other preliminary studies the PhysicianPlus scale which is based on the well-known employees promotor scale was already used in the same setting (Hasebrook et al, 2016b;Hinkelmann et al, 2017;Hahnenkamp et al, 2018) but also in different settings such as the project "rural/rescue". (Hasebrook et al, 2022) Here, the scale was found to be highly reliable with an Cronbach's Alpha of 0.91 while in prior studies in the same present setting, the reliability was examined to lay at 0.78. (Hahnenkamp et al, 2018) In this study, mean ratings show a positive attitude and vary between 1.5 and 3.4 (with 1 o 5 indicating a more positive and 6 to 10 a more negative evaluation) with "purposeful work" being the best and "demanding working hours" the worst evaluation (see table 9).…”
Section: Physicianplus Satisfaction Scalementioning
confidence: 66%
“…The questionnaire consisted of 36 items (Appendix A) and was based on similar questionnaires used in prior studies. These prior versions came with Cronbach's Alpha levels between 0.78 [78] and 0.91 [79]. The survey used in this study also shows a sufficient reliability (Cronbach's Alpha = 0.83).…”
Section: Methodsmentioning
confidence: 81%
“…This summary supports the previous results, that it is easier to predict actual behavior (Table 17, right hand side) than behavioral intention (Table 17, left hand side), and that subjective norm and social orientation play a dominant role in explaining actual green behavior (Table 17, significant beta coefficients, right hand side). The VIF well below 2.5 indicates considerable collinearity of the regression analyses [79]. A summary of all aspects of this study in the format of the study design (see Table 1) is displayed in Figure 4.…”
Section: Model Summary and Model Checkmentioning
confidence: 99%